(untitled) (Tokyo, 1977)
Guides to Japanese Culture is designed to serve two major functions. One is, of course, to provide an authoritative overview of Japanese culture in all its major aspects, as perceived by the Japanese themselves. But the other, and no less important, functon is to demonstrate how a knowledge and appreciation of a foreign culture can point the way to a fresh perspective and can further deepen one's understanding of the many cultural constellations that comprise the world of mankind.